TICS y Educación en Lengua y Literatura de los niños y niñas de septimo año de educación general básica de la Unidad Educativa Dr. Nestor Mogollón López en el périodo lectivo 2016-2017 - Salguero Espín, Jenny del Rocio (2017)
The use of TICS and education in Language and Literature of the children of the seventh year of Basic General Education of the Educational Unit "Dr. Néstor Mogollón López "in the academic period 2016 - 2017; In view of the institution there are a variety of tools for the classroom (HPA) that have not been used to properly use the technologies and improve the teaching process of the Language and Literature area transforming the pedagogical obligation. For this purpose the hypothesis was raised if teachers apply TICS adequately improve the dynamism in the learning of their students; The methodology used was the deductive, descriptive and the method of action, in addition to the types of descriptive research, additional surveys were conducted for teachers, students and parents. The results obtained allowed to know about the incidences of TICS in the teaching-learning processes and the students use the technological tools for entertainment activities, while the teachers have a low level of knowledge about the methodological strategies of the use of TICS, in view of the fact that education in the Dr. Néstor Mogollón López Educational Unit can not be exempt from technological advances, it is suggested the implementation of workshops aimed at teachers on the history of informatics through the use of Smart Art graphics, Blog for the creation of songs, verses, mythologies and legends through the use of slides and proper use of the internet which applied in an appropriate way contributed the best educational quality of this important institution of La Maná town.